Relationship Among Motor Behavior, Motor Development, and Motor Performance in Children Aged 7–8 Years in China - Zhang, Hongbing; Cheng, Jiajia; Wang, Zongping (Frontiers in Public Health, 2022)
For children aged 7–8 years in China, “immobility” is a key problem hindering their physical and mental development in recent years. It is widely accepted that motor performance development in children is accompanied by physical and mental growth and development. However, few studies have clarified the relationship among motor behavior, motor development and motor performance. To bridge this knowledge gap, an empirical analysis of children aged 7–8 years in China was conducted. This study developed scales for testing motor performance, motor behavior and motor performance, respectively, and collected data of these tests on children aged 7–8 years in China. Canonical correlation analysis was used to analyze the correlations among motor performance, motor behavior and motor performance, and partial least squares regression was used to evaluate the relationship between dependent and independent variables. It was found that, for the children aged 7–8 years in China, there were significant positive correlations among the motor performance, motor behavior, and motor development. The three tests were closely related and could be applied to promote children's sports performance through improved training activities for targeting specific indicators. The study found there was no significant differences in the application of the three tests for children with different age and gender. This finding lays a foundation for further testing in older children and meets the measurement requirements of modern medicine's “bio-psycho-social model of health promotion”. Additionally, the theoretical motional quotient model of “The Bio-Behavior-Task” is constructed as a comprehensive motor performance evaluation system, aligning with students' physical and mental development standards.